Hukum Sebagai Senjata Politik dan Fenomena Viralitas Sebagai Senjata Sosial - Aswin, Albert Stephan; Faisal, Sarman; Husain, Alwi (Fakultas Hukum, Universitas Boyolali, 2025)
This writing explores the use of law as a political tool by populist authoritarian leaders in Indonesia, who often enforce it selectively to suppress opposition and protect political allies, undermining the principles of justice and the rule of law. Through the phenomenon of